Isolation and Identification of Flavonoid Compound from Nutmeg Leaves (Myristica fragrans Houtt) - Ginting, Binawati; Marpaung, Lamek; Barus, Tonel; Simanjuntak3, Partomuan (Asian Journal of Chemistry, 2015)
A flavonoid compound i.e. 3,5,7,4'-tetrahydroxy-dihydroflavonol or dihydrocaempferol which has contents an antioxidant activity with IC50 value about 9.75 ppm were successfully isolated and identified. The structures of the obtained compound are identified using spectral data analysis such as ultra-violet, infrared, 1D NMR (1H NMR, 13C NMR), 2D NMR (COSY, HMQC and HMBC) and mass spectra.